Effect of a training program for the development of the relative strength and performance level of elevation the center reverse skill for wrestlers - Abdel-Halim Abdel-Halim, F. (World Journal of Sport Sciences, 2010)
The research has included an introduction and the research problem, as the researcher noted to identify the importance of the relative strength of the arms, legs and back and their effect on performance level of the elevation of the center reverse wrestling. The researcher used the experimental method using the experimental design of two groups, experimental and officer and chose a sample of the research intentional wrestlers under 18 years old and registered the Egyptian Union of Wrestling in 2009 where it reached 18 players were divided into two equal groups and after a process of equality and homogeneity of the two groups. The researcher made a measurement for both the physical tests and skill under the experimental and officer groups by measuring the maximum power of the arms, legs and back to determine the level of relative strength, as well as measuring performance of skills in the elevation of the center and inverse by photographing skillful performance with a competitor negative and competitor positive, then the researcher did the proposed program which took 12 weeks by 4 units a week and the training module was of 120 minutes distributed on the components of the module and researcher did dimensional measurements in the variables under induction and of the results of the program and significant differences between the dimensional measurements for the two experimental and officer groups for the experimental group in the variables of physical and skill under discussion for members of the experimental group.